(untitled) (Medico Legal Update, 2021)
Background: The expectation of a woman during pregnancy is to have a healthy live bay with no complications. Admission of a newborn baby to the newborn unit is distressing to the parents, more so in cases where there is little or no support from the health care team and other players. Objective: To establish factors contributing to emotional distress among postpartum mothers with newborns at newborn unit Kenyatta National Hospital, Kenya. Method: This was a descriptive cross-sectional study employing a quantitative method by use of an interviewer-administered questionnaire. The study was conducted among 59 postpartum mothers with newborns at the Newborn Unit Kenyatta National Hospital. Simple random sampling technique was employed and data collected using a pretested semi-structured questionnaire. Data was analyzed using Statistical Package for The Social SPSS version 25 software. Qualitative data was coded, categorized into themes and thematic analysis done. Results: The factors contributing to maternal emotional distress were low levels of education primary 14(23.7%) and secondary 23(39.0%) and unemployment 27(45.8%). In addition, lengthy NBU stays 34(57.6%), ineffective communication patterns 18(30.5%) and null communication 9(15.3%) between mothers and the healthcare givers contributed to emotional distress. Conclusion: There are sociodemographic, socioeconomic, and hospital factors contributing to maternal emotional distress.